Avanço máxilo-mandibular e reposicionamento simultâneo dos discos articulares: avaliação tridimensional - Porciúncula, Guilherme Machado da [UNESP] (2014)
This study assessed three-‐dimensional displacements and adaptive morphological responses following maxillomandibular advancement (MMA) with or without simultaneous repositioning of the temporomandibular joint (TMJ) articular discs. The sample was composed of CBCT files of cone-‐beam computed tomography images from 32 subjects (23 females and 9 males) that were divided into 2 groups: group 1 (n=12) -‐ subjects without disc displacement underwent MMA with no TMJ intervention; group 2 (n=20) – subjects with bilateral disc displacements underwent MMA with simultaneous TMJ articular disc repositioning. An automatic cranial base superimposition method was used to register the CBCT's files in three time points: T1 (pre-‐surgery), T2 (immediate postoperative) and T3 (at least 11 months follow-‐up). To assess surgical changes (T2-‐T1) and adaptive responses (T3-‐T2), the CBCT's files were compared using the shape correspondence (SPHARM-‐PDM) quantitative method. Statistical analysis was performed by means of Student t test and Pearson correlation coeficient. We observed that surgical displacements (T2-‐ T1) were similar in both groups for all the regions of interest, except the condyles that moved in opposite directions; group 1 (superior and posterior) and group 2 (inferior and anterior). In the longest follow up period (T3-‐T2), we observed large individual variability, with smaller magnitude of change in group 2. Sagittal relapses were similar in both groups and less than 20%. We concluded that maxillomandibular surgical advancement is a stable procedure that promotes condylar displacements immediate after surgey. Articular disc repositioning was beneficial since condylar resorption had lower magnitude in group 2 subjects.